Low SARS-CoV-2 seroprevalence in the Austrian capital after an early governmental lockdown - Marie-Kathrin Breyer (Nature Portfolio, 2021)
Abstract We analyzed SARS-CoV-2 seroprevalence in a large, well-described representative Viennese cohort after an early governmental lockdown with respect to the occurrence of symptoms and household transmission. Participants of the LEAD Study, a population-based cohort study from Vienna, Austria, were invited along with their household members (April 20th to May20th 2020). Sera were analyzed using anti-SARS-CoV-2 immunoassay including a neutralization test as a confirmatory assay. A total of 12,419 individuals participated (5984 LEAD participants; 6435 household members), 163 (1.31%; 59 LEAD cohort members) of whom were SARS-CoV-2 antibody positive. The estimated number of COVID-19 cases projected from our findings by age and sex for Vienna was 21,504 (1.13%). Cumulative number of positively tested cases in Vienna until May 20th 2020 was 3020, hence 7.1 times (95% confidence interval 5.5–9.1) lower than projected. Relative risk (RR) of seropositivity by age was highest for children aged 6–9 years [RR compared to age group 20–49: 1.21 (CI 0.37–4.01)], lowest for ≥ 65 years [RR 0.47 (CI 0.21–1.03)]. Half of the positive individuals developed no or mild symptoms. In a multivariate analysis, taste and smell disturbances were most strongly related to SARS-CoV-2 positivity. Infection probability within households with one confirmed SARS-CoV-2-specific antibody-positive person was 31%. Although seroprevalence was very low (1.13%) for a central European capital city, due to an early governmental lockdown, SARS-CoV-2 infections were more prevalent than officially reported polymerase chain reaction-positive cases. Of note, seroprevalence was highest in young children. Half of SARS-CoV-2 antibody-positive subjects had no or only mild symptoms. Taste and smell disturbances were most prominent, possibly guiding clinicians in diagnosing SARS-CoV-2 infection.